Investigation of ATP Citrate Lyase as a regulator of skeletal muscle nutrient metabolism - Parker, Chanae Ann (My University, 2026)
As global pressures for livestock production grow, establishing innovative ways to improve livestock growth efficiency is imperative to meet the growing global demand for meat. Understanding mechanisms regulating skeletal muscle growth in livestock holds potential to accomplish this feat. This work aims to uncover mechanisms that modulate skeletal muscle metabolism to exploit during postnatal muscle growth of livestock animals. The enzyme ATP Citrate Lyase (ACLY) has been identified as a metabolic regulator in other cell types but has largely been unexplored in skeletal muscle. Our hypothesis is that ACLY dictates nutrient utilization and drives a unique metabolic fingerprint in skeletal muscle. Using an in vitro system, C2C12 myoblasts were transfected with GFP (control) or ACLY plasmids to investigate nutrient utilization in ACLY overexpressing myoblasts. Transfected cells were pulsed with ¹³C₆-glucose or ¹³C₁₆-palmitate to identify ACLY-mediated patterns of glucose utilization and nutrient preference. Myoblasts and culture media were collected and analyzed using gas chromatography-mass spectrometry. Glucose-pulsed myoblasts overexpressing ACLY exhibit a decrease in isotopic enrichment of the glycolytic substrate lactate and of TCA cycle intermediates oxaloacetate, citrate, succinate, [alpha]-ketoglutarate, and fumarate compared to controls (P<0.05). However, glucose uptake and isotopic enrichment of pyruvate were similar in ACLY myoblasts compared to control myoblasts (P>0.05). ACLY-overexpressing palmitate-pulsed myoblasts had decreased isotopic enrichment in lactate, oxaloacetate, citrate, succinate, [alpha]-ketoglutarate, and fumarate (P<0.05) with no change in glucose uptake or isotopic enrichment of pyruvate (P>0.05). These data depict an ACLY-mediated mechanism that regulates nutrient flux through glycolysis and the TCA cycle in skeletal muscle cells without a nutrient shift towards palmitate. Although additional investigation is needed to elucidate this mechanism, ACLY appears to alter substrate allocation and utilization between the two major metabolic pathways and warrants further exploration as a target to improve economic nutrient utilization in growing muscle.
Keywords: Metabolism; ATP Citrate Lyase; Cell culture; C2C12; Hypertrophy